Pengaruh Introduksi Kompos Plus terhadap Produkasi Bobot Kering Daun Kumis Kucing (Orthosiphon aristatus) pada Tiga Macam Media Tanah - Widawati, Sri; Suliasih, Suliasih; Syaifudin, Syaifudin (Perhimpunan Biologi Indonesia, 2002)
ABSTRACTA green house experiment were conducted to study the application of âcompost plusâ on the growth of Orthosiphon aristatus. The experiment was designed in Complete Randomized Design with factorial and five replicates. The first factors were fertilizer application (compost plus, compost, and control). The second factors were 3 kinds of soil (i.e. soil from Cibinong, Ciomas, and Sukabumi). The result showed that compost plus application increased 113.90 gram/pot of dry weight of Orthosispon aristatus leaves compared with compost application and control in 3 kinds of soil.Key words : Compost plus (compost + microbes), Orthosispon aristatus